Islamic Microfinance as a Poverty Reduction Tool in Terms of Islamic Finance: An Analysis of the Islami Bank Microfinance Scheme in Bangladesh - Nahar, Lutfun (CenRaPS Journal of Social Sciences, 2022)
Although Microfinance is one of the essential parts of poverty reduction, however, there are so ‎many microfinance schemes that provided financial help under the various organization models ‎in the world. But a Muslim is not able to benefit from these schemes since most of the time, ‎microfinance schemes are provided into a conventional microfinance system which includes the ‎‎“interest (Riba)” that is strictly prohibited for Muslims. Nevertheless, this study constitutes a ‎linkage between Islamic Finance and IBBL Islamic microfinance scheme, whether it works for alleviating poverty in ‎Bangladesh. As it is known that Islami Bank Bangladesh Limited (IBBL) focused Shariah ‎compliance disclosure by establishing its reputation and differentiating itself from conventional ‎microfinance systems. Accordingly, this article will point out how Islamic microfinance follows ‎the Islamic Shari’ah in its operation and helps clients to improve their moral and ethical values ‎through Rural Development Scheme (RDS), which allows the rural Muslims in Bangladesh to ‎involve in the Islamic microfinance schemes. Applying performance analysis techniques, this ‎article analyzes the status of Rural Development Schemes (RDS) offered by Islami ‎Bank Bangladesh Limited, Bangladesh, where the specific objectives of this study include ‎analyzing the allocation efficiency of RDS, and financial performance (Risk and Return ratios) ‎of RDS of Islami Bank Bangladesh Limited and how it works as an alternative tool for poverty ‎reduction through their various investment models. With this method, this article mainly argues ‎whether Islamic microfinance provides an alternative to poverty reduction. ‎